2013
DOI: 10.1111/acel.12065
|View full text |Cite
|
Sign up to set email alerts
|

Heterochronic parabiosis: historical perspective and methodological considerations for studies of aging and longevity

Abstract: Summary Pairing two animals in parabiosis to test for systemic or circulatory factors from one animal affecting the other animal has been used in scientific studies for at least 150 years. These studies have led to advances in fields as diverse as endocrinology, immunology, and oncology. A variation on the technique, heterochronic parabiosis, whereby two animals of different ages are joined to test for systemic regulators of aspects of aging or age-related diseases also has almost a century-long scientific his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
162
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(164 citation statements)
references
References 29 publications
2
162
0
Order By: Relevance
“…Attempts to track the mechanisms of such interorgan signal transmission have been made using parabiosis, an experimental model in which the circulatory systems of animals of the same or different age (homochronic or heterochronic systems, respectively) were united [46]. In particular, it was found that heterochronic parabiosis enhances the proliferation of neural stem cells in older animals and that these neural stem cells differentiated into neuroblasts and migrated to the olfactory bulb, resulting in a significant increase in the discrimination of smell [47].…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to track the mechanisms of such interorgan signal transmission have been made using parabiosis, an experimental model in which the circulatory systems of animals of the same or different age (homochronic or heterochronic systems, respectively) were united [46]. In particular, it was found that heterochronic parabiosis enhances the proliferation of neural stem cells in older animals and that these neural stem cells differentiated into neuroblasts and migrated to the olfactory bulb, resulting in a significant increase in the discrimination of smell [47].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also clear from heterochronic parabiosis (12)(13)(14)(15)(16)(17) and serum transfer (17,18) studies that cell non-autonomous mechanisms play important roles in suppressing or driving degenerative changes that arise as the consequence of spontaneous, stochastic damage. For example, using heterochronic parabiosis, it was demonstrated that factors in young blood rejuvenate certain cell types and tissues in old mice (12)(13)(14)(15)(16)(17). These anti-geronic factors in young serum include GDF-11 and oxytocin (19).…”
Section: Autonomous and Non-autonomous Mechanisms Of Agingmentioning
confidence: 99%
“…Numerous reports have demonstrated the existence of factors present in the circulatory system of young rodents that can promote tissue regeneration in aged rodents (Lunsford et al ., 1963; Conboy et al ., 2005; Conboy et al ., 2013). GDF11 was recently proposed to decline in concentration in old mice and to restore young tissue function phenotypes in the heart, CNS, and skeletal muscle (Loffredo et al ., 2013; Sinha et al ., 2014).…”
mentioning
confidence: 99%